Topics in cryptology CT-RSA 2011 The cryptographers track at the RSA conference 2011, San Francisco, CA, USA, February 14-18, 2011. Proceedings - Kiayias, Aggelos; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the Cryptographers' Track at the RSA Conference 2011, CT-RSA 2011, held in San Francisco, CA, USA, in February 2011. The 24 revised full papers presented together with 1 invited lecture were carefully reviewed and selected from 79 submissions. The papers are organized in topical sections on secure two-party computation, cryptographic primitives, side channel attacks, authenticated key agreement, proofs of security, block ciphers, security notions, public-key encryption, crypto tools and parameters, and digital signatures.
Electronic reproduction.
Keywords: Electronic books; Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Computational complexity